Design and fabrication of hole cover by casting process - Muhammad Kamili, Zahidi (2011)
This report is an outcome of carrying out and completing the Final Year Project in Diploma Mechanical Engineering. The project entitled Design and Fabricate of Hole Cover by Casting Process. This project focus on redesign electrical output hole cover. The objective of this project is redesigning hole cover with Computer Aid Design (CAD) and fabricating by using casting process. In overall this project started with designing process by using Solid Work software. Then it has followed by casting process. The casting process has a few steps. The first step is making pattern by using wood material. Then preparing mold by using the finished pattern. The process continues with melting the material in furnace and pouring them into mold. After that is cooling the material. The material must be cool sufficiently before remove the mold by wire brush. Lastly is finishing process by machine to remove any excessive material. As the result, a new pattern of electric output hole cover has been designed and fabricated it by casting process. After all the process had been done, this project helps in gaining knowledge about designing by Solid Work software and fabricating by casting process.